Construct Validity Of Ryff's Psychological Wellbeing 18 Items Version Using Confirmatory Factor Analysis (CFA) - Farida Aryani; Nur Fadhilah Umar (Universitas Negeri Makassar, 2022)
Psychological wellbeing is a psychological variable that measures the wellbeing of an individual in his environment. This mental condition can be positive or negative. Based on the psychological wellbeing theory developed by Riffs, there are six dimensions to measure psychological wellbeing, namely Self-Acceptance, Purposes in Life, Environmental Mastery, Positive Relationship, Personal Growth, and Autonomy. Ryff psychological wellbeing consists of 18 items with seven answer choices. The purpose of this study was to test the validity of the instrument construct in several types of respondents, namely teachers/school counsellors, students and employees in South Sulawesi. The analysis technique used is the confirmatory factor analysis (CFA) test with JASP software's help. This study's results indicate that of all 18 items, there are several unidimensional and multidimensional items. Therefore it can be concluded that Ryff's Psychological Well-Being Scale Version 18 cannot measure just one factor.